2007
DOI: 10.1016/j.amc.2007.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Pest regulation by means of impulsive controls

Abstract: In this paper, we consider an integrated pest management model which is impulsively controlled by means of biological and chemical controls. These controls are assumed to act in a periodic fashion, a nonlinear incidence rate being used to account for the dynamics of the disease caused by the application of the biological control. The Floquet theory for impulsive ordinary differential equations is employed to obtain a condition in terms of an inequality involving the total action of the nonlinear force of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 18 publications
(15 reference statements)
2
38
0
Order By: Relevance
“…(A2) The infected pests neither recover nor reproduce; the infected pests neither damage crops nor contribute to the total size of the environment-supported population (this assumption is in line with the findings of Paul et al [6] and Jiao et al [9] who have shown that when insect S 1 is laboratory-infected with disease I 1 , it ceases to reproduce, and when these diseased insects are released into the insect population, crops damage is dramatically reduced). (A3) The incidence rate of the infection is nonlinear in I and given by βS(t)I q (t), q > 0.…”
Section: Model Formulationsupporting
confidence: 72%
“…(A2) The infected pests neither recover nor reproduce; the infected pests neither damage crops nor contribute to the total size of the environment-supported population (this assumption is in line with the findings of Paul et al [6] and Jiao et al [9] who have shown that when insect S 1 is laboratory-infected with disease I 1 , it ceases to reproduce, and when these diseased insects are released into the insect population, crops damage is dramatically reduced). (A3) The incidence rate of the infection is nonlinear in I and given by βS(t)I q (t), q > 0.…”
Section: Model Formulationsupporting
confidence: 72%
“…[7]. The proofs of the above-mentioned results are obvious [14] . Consequently, from the above mathematical results, the pathogenic microorganism-free state will be stabilized by using the appropriate dose of antibiotic injection and the suitable time interval for injection.…”
Section: Remark 21mentioning
confidence: 95%
“…Impulsive differential equations have become more important in recent years in mathematical models of real processes and phenomena studied in control theory [7,8], population dynamics and biotechnology [9,10], physics and mechanics problems [11]. There has been a significant development in the area of impulsive differential equations with fixed moments.…”
mentioning
confidence: 99%